The Conceptual Nexus Between Islamic Foresight, Islamic Thought And The Shariah - Norfadhilah Mohamad Ali; Fadhlina Alias; Hendun Abd Rahman Shah; Muhammad Nizam Awang; Rana Abu-Mounes (USIM PRESS, 2024)
Malaysian Journal of Syariah and Law (MJSL) Volume 12 Issue 1 Page (62-76)